Socioeconomic considerations in biosafety decisionmaking: Methods and implementation - Horna, Daniela; Zambrano, Patricia; Falck-Zepeda, José B. (International Food Policy Research Institute, 2013)
Despite the ongoing controversy over their use, genetically modified (GM) crops have progressively grown in popularity and are now planted in approximately 160 million hectares in 29 countries. In the discussions of biosafety regulations for GM crops and whether to approve such crops for commercialization, many countries, including some African nations, have gone beyond environmental assessments and are now introducing socioeconomic considerations as part of their decisionmaking process. There are, however, very few guidelines on how to ensure that this inclusion of socioeconomic considerations results in a robust and efficient decisionmaking process. Socioeconomic Considerations in Biosafety Decisionmaking: Methods and Implementation provides guidance to professionals involved in assessing the ex ante impact of a GM crop in the context of an approval process. Using the case of GM cotton in Uganda, the authors illustrate the evaluation of socioeconomic impact on farmers, the national economy, and trade.